Design of Web-Based Online Counseling Application at SMA N 6 Tasikmalaya - Faturahman, Muhammad Rizqi; Sundari, Shinta Siti; Hikmatyar, Missi (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2024)
Abstract—Introduction/Main Objectives: The system for recording student counseling history at SMA N 6 Tasikmalaya still uses print or manual media. This will of course lead to inefficiencies in data archiving. Apart from that, the large number of students is an obstacle for guidance and counseling teachers in guidance and counseling services, especially in handling the schedule for accepting counseling students at the same time. Similar studies have similarities but most focus only on the management of student history records in counseling guidance and students cannot interact online with guidance and counseling teachers. The aim of this research is to create an interactive system for teachers and students so that they can submit counseling schedules online via chat as well as a web-based valid student point recording system. Research Methods: This system uses the PHP programming language with the Laravel framework, the database used by MySQL for design uses the SDLC Waterfall method which uses UML, Class Diagrams, Activity Diagrams and Sequence Diagrams. Finding/Results: The results of the research show that it can increase effectiveness and efficiency in both recording and submitting counseling guidance and students can carry out online counseling via chat.